The effect of fluoride iontophoresis on seal ability of self-etch adhesive in human dentin in vitro - Kanittha Kijsamanmith; Parintorn Wallanon; Chanya Pitchayasatit; Poonnapha Kittiratanaviwat (BMC, 2022)
Abstract Background Fluoride iontophoresis (FI) is a non-invasive method for the transfer of fluoride ions under electrical pressure into dental hard tissue. This study aimed to determine the effect of FI on the seal ability of self-etch adhesive in human dentin using dentin permeability test and scanning electron microscopy (SEM). Methods The experiments were divided into 2 series: series 1 was performed on 28 extracted intact third molars and series 2 was performed on 28 extracted carious third molars (ICDAS 4 and 5). In each series, 20 teeth were used for dentin permeability test and 8 teeth were used for SEM study. For dentin permeability test, the specimens were divided into dentin without FI (control) and dentin with FI (experimental) subgroups. Hydraulic conductance (HD) of dentin was measured before and after adhesive treatment, and calculated for the percentage decrease of HD in each subgroup. Two-way ANOVA and Tukey test were used for statistical analysis. SEM study was used to assess the seal ability of self-etch adhesive and penetration of fluoride ions into dentinal tubules. Results HD after self-etch adhesive treatment reduced by 57.75 ± 17.99% in intact dentin with FI, 46.60 ± 17.03% in intact dentin without FI, 45.00 ± 15.30% in caries affected dentin without FI, and 37.28 ± 14.72% in caries affected dentin with FI. There was no significant difference in percentage decrease of HD between dentin without FI and dentin with FI (P = 0.742); meanwhile, intact dentin with FI had significant greater percentage decrease than caries affected dentin with FI (P < 0.05). SEM findings showed FI produced more particle formation and deeper precipitation in intact dentin than those in caries affected dentin. Conclusions FI did not affect the seal ability of self-etch adhesive in human dentin when compared to without FI. However, FI could augment the seal ability of the self-etch adhesive in intact dentin better than that in caries affected dentin.